Efisiensi Energi Melalui Wireless Charging pada Smart Watch - Muhammad Bayu Adi Negoro; Setyorini; Erwid Musthofa Jadied (LOGIC: Jurnal Penelitian Informatika, 2024)
Nowadays we always need technology, one of which is a smartwatch, nowadays the relationship of this kind of devicewith the natural environment is becoming more important to study because the power extraction that is commonly usedis through non-renewable energy. Recently, there has been a shift in the way batteries are charged on some devices,including smartwatches, from wired to wireless charging. Wireless Charging is considered a transformational technology inthe world, many major manufacturers have invested in this technology. However, the current wireless charging mechanism isconsidered slow and energy inefficient compared to wired charging. Such inefficiencies may in turn exacerbate the adverseimpact of smartwatches on the environment. This paper addresses the issue of energy inefficiency during wireless chargingof smartwatches by comparing different charging practices to identify energy saving opportunities. Overall the wireless offstate charging experiment was found to be more energy efficient than the other two states potentially saving 0.098 Wh andlikewise the wired based charging potentially saving 0.096 Wh . The highest average energy consumption in wired andwireless charging occurs when the smartwatch is ON + WiFiON where wireless charging consumes 0.228 Wh while wiredcharging consumes 0.205 Wh.